THE EFFECT OF BUSINESS ETHICS ON TAX COMPLIANCE WITH TAX MANDATORY KNOWLEDGE AS MODERATING VARIABLES - Yuhanitha, Nensya; Dongoran, Johnson; Elnanto, Johanna Gracelia; Tetelepta, Aditya Antoni (2020)
The purpose of this study is to determine the effect of business ethics of taxpayers on tax compliance by knowing the effect of taxpayer knowledge as a moderating variable in KPP Pratama Salatiga. The population of SMEs (Small and Medium Enterprises) in Salatiga is 1,450 and the number of samples is 100 respondents obtained from the Slovin formula with an error tolerance of 1%. Respondent criteria based on gender, age, type of business, and income. Simple linear regression to show the influence of business ethics of taxpayers on tax compliance in Salatiga. Tax Office is to have a positive and significant effect. Regression moderation to show the results that the knowledge of taxpayers can moderate the influence of taxpayer’s business ethics on taxpayer compliance in the Salatiga Tax Office.